Assessment of medium-term cardiovascular disease risk after Japan's 2011 Fukushima Daiichi nuclear accident: a retrospective analysis. Issue 12 (22nd December 2017) - Toda, Haruka; Nomura, Shuhei; Gilmour, Stuart; Tsubokura, Masaharu; Oikawa, Tomoyoshi; Lee, Kiwon; Kiyabu, Grace Y; Shibuya, Kenji
Abstract : Objective: To assess the medium-term indirect impact of the 2011 Fukushima Daiichi nuclear accident on cardiovascular disease (CVD) risks and to identify whether risk factors for CVD changed after the accident. Participants: Residents aged 40 years and over participating in annual public health check-ups from 2009 to 2012, administered by Minamisoma city, located about 10 to 40 km from the Fukushima Daiichi nuclear plant. Methods: The sex-specific Framingham CVD risk score was considered as the outcome measure and was compared before (2009–2010) and after the accident (2011–2012). A multivariate regression analysis was employed to evaluate risk factors for CVD. Results: Data from 563 individuals (60.2% women) aged 40 to 74 years who participated in the check-ups throughout the study period was analysed. After adjusting for covariates, no statistically significant change was identified in the CVD risk score postaccident in both sexes, which may suggest no obvious medium-term health impact of the Fukushima nuclear accident on CVD risk. The risk factors for CVD and their magnitude and direction (positive/negative) did not change after the accident. Conclusions: There was no obvious increase in CVD risks in Minamisoma city, which may indicate successful management of health risks associated with CVD in the study sample.